Leadership development program and leaders performance for mid-level managers in Saudi Petroleum Company, ARAMCO - Saeed Hameed Aldulaimi (Arab Economic and Business Journal, 2018)
Organizations continually try to increase the level of leadership capability and increase the number of qualified applicants for leadership positions by supporting leadership development training program. This qualitative case study discovers whether participating in a leadership development program resulted in leader's performance that can fill leadership gaps. The theoretical framework of this study is depend on expectancy theory, suggests that leaders who involved in leadership development expect to become leaders in future. This exploratory case study sought to learn whether, upon completion of a comprehensive leadership development program, participants applied for, and assumed, leadership positions. A purposeful sample of 32 participants was drawn from in structured interviews conducted by the researcher from Aramco Company. The results provided evidence that using leadership development programs to fill a leadership gap is productive, and that the effectiveness of this strategy is enhanced when organizations purposefully select and support participants through all stages of their leadership development. Participants who pursued leadership opportunities indicated the importance of institutional involvement in leadership development.
Keywords: 650; Leadership; Development program; Mid-level administrators; Performance; KSA